Examining Parent-Child Contact Practices Among Incarcerated Parents With Mental Health Illnesses - Ahlin, Eileen (Crime & delinquency, 2025)
While there is a growing body of research on parent-child visitation among the general carceral population, less attention has been paid to examining parent-child contact practices among parents with mental health illness diagnoses. The current study uses a sample from the 2016 Survey of Prison Inmates to analyze the associations between mental health illness diagnosis and various modalities of parent-child contact. Multivariate analyses of types of mental health illness diagnoses on six parent-child contact modalities demonstrate heterogeneity where not all mental health diagnoses reduce all parent-child contacts. Furthermore, incarcerated parents with multiple mental health illnesses are less likely to experience most forms of contact including in-person visits, phone calls, and mail.